A política nacional de humanização e suas diretrizes acolhimento e cogestão : a perspectiva de gestores municipais de saúde - Camacho, Gabriela Alvarez (2016)
The National Humanization Policy (PNH ) is considered a proposed policy readjustment Health System (SUS) from the perspective of promoting the autonomy of the actors involved: users, health worker and manager. Profile and abilities of municipalities have impact on health policy processes and promoting function of managers on these aimed to identify the perceptions and actions of managers at the cities level on the PNH , user embracement and the co-management. It is an exploratory research with qualitative approach whose data processing was due to the thematic analysis. Data production took place through individual interviews, oriented from semi-structured, with directors/health and a member of the 06 municipalities management team of a health region secretaries belonging to a Regional Department of Health's State of São Paulo, totaling 12 participants. The results demonstrates how that the managers, in general, are unaware of the PNH and user embracement and co-management. This study showed that decision-making processes within the territories of municipalities still reproduce centralizing management models, in which users and workers are not considered, and that this configuration reflects the context of health in the municipalities. Although it was possible to identify management practices concerned with little inclusive and democratic models as opposed to proposing the PNH.